PLGA protein nanocarriers with tailor-made fluorescence/MRI/PET imaging modalities. Issue 8 (14th February 2020) - Zhang, Yajie; García-Gabilondo, Miguel; Grayston, Alba; Feiner, Irene V. J.; Anton-Sales, Irene; Loiola, Rodrigo A.; Llop, Jordi; Ramos-Cabrer, Pedro; Barba, Ignasi; Garcia-Dorado, David; Gosselet, Fabien; Rosell, Anna; et al.
Abstract : Integrating multimodal imaging modalities in PLGA protein carriers. Abstract : Designing theranostic nanocarriers with high protein payload and multimodality tracking without cross interferences between the different imaging probes and the delicate protein cargo is challenging. Here, chemical modifications of poly(lactic- co -glycolic acid) (PLGA) to produce nanocapsules (NCs) that incorporate several imaging moieties are reported. The biocompatible and biodegradable PLGA-NCs can be endowed with a magnetic resonance imaging (MRI) reporter, two fluorescence imaging probes (blue/NIR) and a positron emission tomography (PET) reporter. The modular integration of these imaging moieties into the shell of the NCs is successfully achieved without affecting the morphochemical properties of the nanocarrier or the protein loading capacity. In vivo biodistribution of the NCs is monitored by MRI, PET and NIRF and the results from different techniques are analyzed comparatively. The viabilities of two different human endothelial cells in vitro show no toxicity for NC concentration up to 100 μg mL −1 . The morbidity of mice for 2 weeks after systemic administration and the hepatic/pancreatic enzymes at the plasma level indicate their in vivo biosafety. In summary, the new theranostic PLGA nanoplatform presented here shows versatile in vitro / in vivo multimodal imaging capabilities, excellent biosafety and over 1 wt% protein loading.